Apego emocional en niños según el estilo de crianza - Muñoz Abarca, Daniela Jhemilec (2023)
We call the affective relationship between the mother or caregiver and the newborn attachment. Its purpose is to ensure care, psychological development, and personality formation. In the first years of life, attachment develops through two systems: the exploratory system, which allows the baby to interact with its environment through the senses, and the affiliative system, which facilitates contact with other people. It is noteworthy to mention that we achieve this system development through parenting; it is a continuous process that spans from infancy to adulthood, where parents or guardians take care of the child. It requires a significant physical and emotional effort due to the physical and emotional immaturity of the human being at birth since they cannot satisfy their own needs independently. The purpose of the present research work was to describe the scientific evidence regarding the type of emotional attachment according to the mothering style in children; we carried out the methodological course under a qualitative approach of descriptive documentary type, non-experimental design of transversal crossover criterion non-probabilistic sample by convenience within the guidelines of inclusion and exclusion, documents that have the variables under study, child population, articles within Latin America and, must be published within the last 20 years, that is to say from 2003 to 2023. We highlighted four results: 1) secure attachment has a relationship with the democratic parenting style, 2) insecure-ambivalent attachment is related to the permissive parenting style, 3) insecure-disorganized attachment is related to the authoritarian parenting style, and 4) insecure-avoidant attachment is related to the neglectful parenting style. The data collected showed that children with insecure attachments tend to develop psychological problems, social interaction, self-esteem, independence, and confidence. On the other hand, secure attachment indicates greater confidence, autonomy, and stability in both personal and interpersonal development